1967
DOI: 10.1063/1.1840572
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Matrix-Isolated Dichlorine Monoxide: Infrared Spectra of ClClO and (ClO)2

Abstract: Articles you may be interested inPressure dependence and metastable state formation in the photolysis of dichlorine monoxide (Cl2O)In situ photolysis of matrix-isolated dichlorine monoxide, CbO, at 20 o K, produced eight bands near 960 cm-1 and a quartet near 375 cm-I • Growth plots for the high-frequency features during photolysis show that three distinct molecules are produced. Oxygen and chlorine isotopic shifts indicate that CICIO, with a structure like those of the nitrosyl halides, is most probably respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
1

Year Published

1972
1972
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 27 publications
1
40
1
Order By: Relevance
“…The electron spin resonance of the radical has been observed both in rigid solution [16] and in the gas phase [17,18]. Infrared study by the method of matrix iso'lation [19] has identified the dimer, Cl 2 0 2 , but not the radical, ClO.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The electron spin resonance of the radical has been observed both in rigid solution [16] and in the gas phase [17,18]. Infrared study by the method of matrix iso'lation [19] has identified the dimer, Cl 2 0 2 , but not the radical, ClO.…”
Section: Discussionmentioning
confidence: 93%
“…Cole [21] detected an electron spin resonance ascribed to ClOO in an irradiated perchlorate single crystal, and another electron spin resonance was tentatively ascribed to it [16]. In a matrix isolation study, Rochkind and Pimentel [19] assigned a pair of infrared absorption bands to ClOO; and a positive identification of ClOO in an argon matrix was made by Arkell and Schwager [22] in an infrared study. Gaseous ClOO was observed in the infrared region by Van den Bogaerde [2] and in the ultraviolet region by Morris [5], both by the molecular modulation method.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Photoexcitation of gaseous OClO results predominately in the formation of ClO and O, with a small amount of Cl and O 2 also produced. [5][6][7] However, the photochemical production of the ClOO isomer is observed in low-temperature matrixes, [8][9][10] and photolysis of solution-phase OClO results in both ClO/O and ClOO production. [11][12][13][14][15][16][17][18][19][20][21] Another halooxide, dichlorine monoxide (ClOCl), demonstrates phase-dependent photochemical reactivity similar to OClO.…”
Section: Introductionmentioning
confidence: 99%
“…In the gas phase, direct dissociation to form Cl and ClO is the dominant photochemical pathway, [22][23][24][25][26][27][28][29][30] whereas, photoexcitation in low-temperature matrixes and in solution results in the formation of the isomer, ClClO. 9,[31][32][33][34][35] Given the substantial information regarding the phasedependent photochemical reactivity of halooxides, it is reasonable to ask if similar environment-dependent reactivity is observed for related compounds. To address this question, we have investigated the condensed-phase photochemistry of nitrosyl chloride (ClNO).…”
Section: Introductionmentioning
confidence: 99%
“…
There have been many experimental studies of the photolysis of dichlorine monoxide (Cl 2 O), [1][2][3][4][5][6][7][8] Meanwhile, the direct isomerization from ClOCl into ClClO through a transition state (TS S0 ) of S 0 was also suggested in 1998, 5 as another possible explanation for the isomer, but the role of TS S0 in actual dynamical process has not yet been clearly studied theoretically. A later theoretical study in 2001 with reduced two-dimensional space at fixed bond angle showed that the initial dynamics of excited electronic states is the direct dissociation of ClOCl to ClO and Cl, 6 but the possibility of isomerization through angular motion in either the ground or the excited electronic state was not explicitly studied there.
…”
mentioning
confidence: 99%